DeepL app: Effect on students’ vocabulary mastery - Taufiqurrohman, Muhammad; Sofiana, Nina (Indonesian Journal of Educational Development (IJED), 2025)
In the digital era, improving English vocabulary acquisition through technology-based tools has become increasingly urgent to meet the demands of modern language learning and curriculum integration. The research group investigated the impact of the DeepL app on students' vocabulary acquisition, noting that this interactive educational tool can also enhance vocabulary skills. However, research specifically examining the effect of DeepL apps on vocabulary acquisition is limited. This study aims to investigate the extent to which DeepL apps influence English vocabulary acquisition. This study used a quasi-experimental approach, involving 36 grade 10 students at MA Miftahul Ulum in the academic year 2024/2025. The study was divided into two groups, an experimental group and a control group. Eighteen students from class X IPS 1 participated in the experiment, while eighteen students from class X IPS 2 were placed in the control group. Pre-tests and Post-tests, consisting of a total of 20 valid multiple-choice questions, were among the data collection instruments. To verify the hypothesis, the researcher employed the independent sample t-test tool in SPSS 26. The mean post-test score of the experimental class was 88.06, while that of the control group was 70.56. Furthermore, the independent sample t-test findings revealed that the significant value (sig.) exceeded 0.05, specifically 6.525 (6.525 > 0.05), indicating that the DeepL application positively impacted students' vocabulary acquisition. This study highlights the potential of the app-based learning tool DeepL in improving educational outcomes related to vocabulary.